Beyond the individual: Governing AI's societal harm - Nathalie A. Smuha (Internet Policy Review, 2021)
In this paper, I distinguish three types of harm that can arise in the context of artificial intelligence (AI): individual harm, collective harm and societal harm. Societal harm is often overlooked, yet not reducible to the two former types of harm. Moreover, mechanisms to tackle individual and collective harm raised by AI are not always suitable to counter societal harm. As a result, policymakers' gap analysis of the current legal framework for AI not only risks being incomplete, but proposals for new legislation to bridge these gaps may also inadequately protect societal interests that are adversely impacted by AI. By conceptualising AI's societal harm, I argue that a shift in perspective is needed beyond the individual, towards a regulatory approach of AI that addresses its effects on society at large. Drawing on a legal domain specifically aimed at protecting a societal interest-environmental law-I identify three "societal" mechanisms that EU policymakers should consider in the context of AI. These concern (1) public oversight mechanisms to increase accountability, including mandatory impact assessments with the opportunity to provide societal feedback; (2) public monitoring mechanisms to ensure independent information gathering and dissemination about AI's societal impact; and (3) the introduction of procedural rights with a societal dimension, including a right to access to information, access to justice, and participation in public decision-making on AI, regardless of the demonstration of individual harm. Finally, I consider to what extent the European Commission's new proposal for an AI regulation takes these mechanisms into consideration, before offering concluding remarks.
Keywords: 300; Artificial intelligence; Society; Environmental law; EU law; AI governance